Contextualist Approaches and the Interpretation of the Qur’ān - Abdullah Saeed; Ali Akbar (Religions, 2021)
When it comes to the interpretation of ethico-legal texts in the Qur’ān, there is usually a high degree of emphasis on literalism and textualism but not enough focus on contextualization. This is true for both the classical period and the modern period. This article points to the contextual nature of interpretation and how the contextualist approach to interpreting the Qur’ān can enable Muslims to follow its ethical teachings in accordance with contemporary needs and circumstances, without sacrificing fundamental Qur’ānic values. In order to do so, the article refers to Qur’ānic passages related to freedom of religion and the laws of punishment, and explores how a contextualist approach to interpreting such passages may yield results different from those of a textualist or literalist approach.